Development of Chemical Management System for UTHM - Murugan, Puvanasundari; Suhaila Mohd.Yasin, (Applied Information Technology And Computer Science, 2022)
UTHM Chemical Management System is the main platform for all chemical applications, registrations and handle all processes. The existing system records and manages all chemical information manually using a filing system. Next, all the chemical record is not centralized and is less accessible by the current administration as well as the manual filing may sometimes cause the SDS to be missing. Therefore, a web-based UTHM Chemical Management System is developed using structured method. The system contains available chemical module, chemical application, chemical registration module, report generation module and supplier module. The Incremental Development Model is used as the methodology during the development of this system. This system is expected to change the current system from manual into a web-based system as well as increase UTHM OSHE's accessibility to all chemicals' information. At the end of this project, UTHM Chemical Management System can switch from a manual to a web-based system.